"INNOVATIVE METHODS OF DISTANCE FOREIGN LANGUAGE LEARNING IN HIGHER EDUCATION INSTITUTIONS" - Shavkat Akhmatovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Modern higher education is increasingly focused on the use of innovative methods and technologies, especially in the field of foreign language teaching. With the development of information technology, distance learning has become an essential part of the educational process, providing students the opportunity to study languages in a format and at a pace that suits them. The introduction of new digital tools—such as online platforms, virtual classrooms, mobile applications, and artificial intelligence—opens new horizons for language learning, making the process more flexible, accessible, and personalized.